2023
DOI: 10.3390/vaccines11101514
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Influenza Vaccination Attitudes and Actions in Spain’s Adult Population

Camino Prada-García,
Marina Toquero-Asensio,
Virginia Fernández-Espinilla
et al.

Abstract: Seasonal influenza is an acute respiratory infection caused by the influenza virus which constitutes a significant public health issue associated with high morbidity and mortality. The aim of this study was to investigate changes in attitudes, perceptions, and practices regarding influenza vaccination in the Spanish adult population during the COVID-19 pandemic, as well as their vaccination intentions, with special attention paid to those over 65 years old and in high-risk groups. To this end, a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Delving into participants’ arguments about abstinence, thematic content analysis revealed themes that fit the proposed “3Cs” (confidence, convenience, complacency) and “5Cs” (confidence, convenience, complacency, calculation, collective responsibility) models exploring vaccine hesitancy [ 4 , 43 ]: disbelief in effectiveness, fear of side effects, mistrust in institutions and policy practices (“confidence”), low susceptibility to disease (“complacency”), negligence (“convenience”), absence of health professionals’ recommendation and insufficient information (“calculation”). In line with previous studies, doubting the effectiveness of vaccines acts as a major deterrent in curbing immunization efforts [ 34 , 35 , 44 , 45 , 46 , 47 , 48 ], as is participants’ belief in good health and thus low perceived risk of vaccine-preventable diseases [ 34 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Lack of advice, endorsement and guidance by health professionals reduces vaccine uptake [ 35 , 41 , 48 , 50 , 51 , 52 ], as is insufficient information about preventable diseases and the respective vaccines [ 46 , 47 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Delving into participants’ arguments about abstinence, thematic content analysis revealed themes that fit the proposed “3Cs” (confidence, convenience, complacency) and “5Cs” (confidence, convenience, complacency, calculation, collective responsibility) models exploring vaccine hesitancy [ 4 , 43 ]: disbelief in effectiveness, fear of side effects, mistrust in institutions and policy practices (“confidence”), low susceptibility to disease (“complacency”), negligence (“convenience”), absence of health professionals’ recommendation and insufficient information (“calculation”). In line with previous studies, doubting the effectiveness of vaccines acts as a major deterrent in curbing immunization efforts [ 34 , 35 , 44 , 45 , 46 , 47 , 48 ], as is participants’ belief in good health and thus low perceived risk of vaccine-preventable diseases [ 34 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Lack of advice, endorsement and guidance by health professionals reduces vaccine uptake [ 35 , 41 , 48 , 50 , 51 , 52 ], as is insufficient information about preventable diseases and the respective vaccines [ 46 , 47 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 84%
“…In line with previous studies, doubting the effectiveness of vaccines acts as a major deterrent in curbing immunization efforts [ 34 , 35 , 44 , 45 , 46 , 47 , 48 ], as is participants’ belief in good health and thus low perceived risk of vaccine-preventable diseases [ 34 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Lack of advice, endorsement and guidance by health professionals reduces vaccine uptake [ 35 , 41 , 48 , 50 , 51 , 52 ], as is insufficient information about preventable diseases and the respective vaccines [ 46 , 47 , 51 , 52 ]. Our participants highlighted negligence as the root of no uptake and committed to prompt immunization, an argument also expressed in previous studies [ 41 , 46 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Conclusively, we found that patients who were willing to get vaccinated against COVID-19 were also more likely to be vaccinated against influenza and pneumococci. The impact of the pandemic on individual perceptions increasing vaccination awareness and uptake has recently been reported by others [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 87%